2015
DOI: 10.1007/s40171-015-0118-9
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Management Approach for Globally Distributed Software Projects

Abstract: Management of globally distributed software projects is one of the biggest challenges of the IT industry worldwide. Distributed software development involves teams working in different geographic locations and even in different countries. These distributed projects may involve teams from the same organization or have collaborative teams from different organizations that work together on a specific project. The dimension of distribution greatly enhances the complexity of managing these projects in globalized wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…To align project objectives with project stakeholders, project flexibility offers an effective approach by not violating the project's previous decisions (Floricel et al, 2012). Project flexibility eliminates the uncertainty and complexity by mitigating the risks in a dynamic environment (especially in project-based organizations) and protects organizations from uncontrollable consequences (Nandakumar et al, 2013;Yadav, 2016;Zailani et al, 2016;Patil and Suresh 2019). Therefore, organizations should aim to achieve greater flexibility where higher level of uncertainty exists and project effectiveness needs to be improved (Shahu et al, 2013;Pollack and Adler, 2014;Brink, 2017;Nasr et al, 2020).…”
Section: Project Flexibilitymentioning
confidence: 99%
“…To align project objectives with project stakeholders, project flexibility offers an effective approach by not violating the project's previous decisions (Floricel et al, 2012). Project flexibility eliminates the uncertainty and complexity by mitigating the risks in a dynamic environment (especially in project-based organizations) and protects organizations from uncontrollable consequences (Nandakumar et al, 2013;Yadav, 2016;Zailani et al, 2016;Patil and Suresh 2019). Therefore, organizations should aim to achieve greater flexibility where higher level of uncertainty exists and project effectiveness needs to be improved (Shahu et al, 2013;Pollack and Adler, 2014;Brink, 2017;Nasr et al, 2020).…”
Section: Project Flexibilitymentioning
confidence: 99%
“…This research aims at studying the effect of project management flexibility in early project phases on end-project performance, including the effect of project complexity on performance. According to what literature suggests regarding the necessity of making project management more flexible (Ahrens and Chapman, 2004;Geraldi, 2008;Kreiner, 1995;Olsson, 2006;Osipova and Eriksson, 2013;Wirkus, 2016;Wysocki, 2007;Yadav, 2016), a main hypothesis to be tested was formulated as: "flexible project management in early project phases has a positive effect on end-project performance." This hypothesis is shown in the conceptual model (Figure 1) as the arrow from flexible project management to project performance (arrow a).…”
Section: The Effect Of Flexibility On Project Performancementioning
confidence: 99%
“…One of the early definitions of flexibility is provided by Bateson (1972). He defined flexibility as “uncommitted potentiality for change.” Olsson (2006) brings the definition of flexibility based on Husby et al as “the capability to adjust the project to prospective consequences of uncertain circumstances within the context of the project.” Yadav (2016) defines flexibility as: “including adaptiveness to the dynamic environment, responsiveness to change, non-rigidity in processes, variability of parameters and specifications, informal practices that allow for adjustment, autonomy of function, agility in action, customized solutions, and responding to changing customer requirements.”…”
Section: Literature Reviewmentioning
confidence: 99%
“…This suggests that factors that enhance job engagement goes beyond job characteristics and encompasses individual resources and the work environment created by the organization (Lee and Ok 2015). Rastogi et al (2016) and Yadav (2016) suggested that one way of managing talents and enhance job engagement in an organization is to adopt temporal and operational flexibility. Since talents in professional service firms need to feel a sense of belonging to maximally deliver, it then follows that adoption of flexible human resource management measures is key in such organizations.…”
Section: Introductionmentioning
confidence: 99%